A Descriptive Study of Adverse Events from Clenbuterol Misuse and Abuse for Weight Loss and Bodybuilding. Issue 3 (July 2013) - Spiller, Henry A.; James, Kyla J.; Scholzen, Steven; Borys, Douglas J.
Background: Clenbuterol is a β2 -agonist approved in the United States for veterinary use in nonfood animals. Clenbuterol use is emerging among bodybuilders and fitness enthusiasts attracted to the hypertrophic and lipolytic effects. Cases: This was a retrospective chart review of clenbuterol exposures reported to 2 poison control centers. Misuse of clenbuterol for weight loss and bodybuilding was reported in 11 of 13 clenbuterol users. Reported clinical effects included tachycardia, widened pulse pressure, tachypnea, hypokalemia, hyperglycemia, ST changes on electrocardiogram (ECG), elevated troponin, elevated creatine phosphokinase (CPK), palpitations, chest pain, and tremor. Measured serum clenbuterol concentration was 2983 pg/mL post 4.5 mg ingestion. Coingestants included T3 and anabolic steroids. Treatments included activated charcoal, benzodiazepines, β-blockers, potassium replacement, and intravenous (IV) fluid. Conclusions: There is an increasing use of the Internet for illicit drug use for bodybuilding and weight loss purposes. These patients may not present as the stereotype of illicit drug abusers, but as healthy athletic low-risk patients. Clinical effects persisted greater than 24 hours with evidence of myocardial injury in 2 patients. Clenbuterol is increasingly being abused within the bodybuilding subculture. These cases illustrate the hidden dangers of clenbuterol abuse among bodybuilders and fitness enthusiasts.